ARTIFICIAL INTELLIGENCE (AI) IN COMMUNICATION: NAVIGATING THE TOOL-WEAPON SPECTRUM OF ENVIRONMENTAL SUSTAINABILITY IN NIGERIA - ivwighren, hannah Emuobosa; OGIDIAGBA, Freeborn Omuvwie; OKUCHEMIYA, Success; MUKORO, Valerie Oghenetejiri (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study investigated the multifaceted impact of Artificial Intelligence (AI) technology on environmental sustainability in Abraka Metropolis within Delta State Nigeria. It analyses how AI functions as both a powerful instrument and a potential weapon to impact public comprehension and behavioural participation at the nexus of communication studies and environmental concerns. Rationale by the media ecology theory, a mixed-methods research design necessitates the application of primary and secondary data. The population of the study is Abraka Metropolis residents. A sample of 150 respondents within and around Delta State University, Abraka were tested using a purposive sampling technique to reach experts, while a random sampling technique was used for surveying the public. Data collection methods include the use of questionnaires and interviews. For deeper insight into the subject matter, Key Informant Interviews (KII) were conducted with communication, environmental and AI technology experts within and around Delta State University Abraka. For data analysis, descriptive statistics summarized the analysed data, and the hypothesis was tested with inferential statistics using Spearman Rank on the Software app STATA 15.0 to analyse the data. This study concludes that AI technology creates numerous prospects for environmental sustainability communication, challenges such as deep-fake technology, algorithmic bias, and misleading AI-generated content could undermine public trust in environmental sustainability messages. It is recommended that stakeholders in communication and constituted authorities should strengthen AI literacy, enhance AI regulations, improve AI accessibility, integrate AI with human-led interventions, and encourage ethical AI development to develop both information and engagement regarding the preservation of humanity